Programming LEGO® EV3 My Blocks Teaching Concepts and Preparing for FLL® Competition - Harding, Gene (Apress, 2018)
Program Lego® My Blocks to accurately perform navigation functions on competition mats, such as moving forward and backward quickly and precisely, turning, following walls, and following lines. This book features extensive illustrations help to bring each step and concept to life so that you can easily follow along. You'll start by moving your creations forward and backward accurate distances while maintaining directional accuracy. You'll then build My Blocks to turn left and right at precise angles. After that you're creations will be ready to find, follow, and otherwise use lines on the mat to improve navigation accuracy. Finally, you'll delve into using game board border walls to navigate and advanced topics, such as handoffs at speed and accelerating/decelerating to enable higher speed while maintaining navigation accuracy. This book addresses EV3 programming in the specific context of FLL® competition. With Programming Lego® EV3 My Blocks, you will be game-ready to manage the season, prepare for competition, and compete!